P-135 Clinical outcomes depending on post-warming culture duration of vitrified-warmed single blastocyst transfer cycles. (30th June 2022) - Errazuriz, J; Alwane, E; Filselcker, I; Durruty, G; Sanhueza, P; Gonzalez, P; Donoso, P
Abstract: Study question: What is the impact of post-warming blastocysts after very short-term culture (<2 hours) or short-term culture (2–4 hours) on the clinical outcomes? Summary answer: The clinical outcomes of very short-term culture and short-term culture were not significantly different in vitrified-warmed blastocyst transfer. What is known already: In vitrified-warmed blastocyst transfer (VBT), complete blastomere survival and mitotic resumption during warming are generally considered to be the most important factors affecting pregnancy outcomes. It has been assumed that a sufficient warming time may be required for resumption of cell proliferation and development. Currently there is evidence that suggests a minimum mean time of 2.70 ± 1.20 necessary to complete the re-expansion of the embryo that allows evaluating its adequate development. However, the effect of culture duration on pregnancy outcomes in VBT remains controversial. Study design, size, duration: A retrospective observational study was carried out, with all the patients who had frozen-thawed embryos transferred between January and December 202, in Clínica Alemana, Santiago, Chile. The average standard time for embryo thawing in our center is 2 hours. However, on certain occasions, due to its insufficient development and the pressing schedule of surgery rooms, a second embryo must be thawed, usually in less than 2 hours. Participants/materials, setting, methods: Embryos were divided into two study groups depending on whether their post-warming culture period was very short-term (<2 hours) or short-term culture (2–4 hours). Only transfers of 1 embryo on day 5-6 were included. Embryo morphology was analyzed with a Garner microscope score to estimate the quality of the embryos in both groups. Main results and the role of chance: During the study period, a total of 127 single VBT cycles were included: 48 in the very short-term group and 79 in the short-term group. Patients' demographic characteristics did not significantly differ between the groups. (Age 34.9±3.6 vs 35±3.4, p =0.89; Infertility duration (yr) 2.75±1.1 vs 2.5 ±1.1, p =0.24; AMH 2.1 [0.2-5.4] vs 2.1 [0.2-5], p =0.84) An analysis of previous fresh in vitro fertilization cycles and subsequent VBT cycle parameters revealed no differences in the number of retrieved oocytes (11.7 vs 12, p =0.74), the number of fertilized oocytes (8.6 vs 8.5, p =0.86), the number of vitrified blastocysts (3.4 vs 3.6, p =0.87) and in both groups. The clinical pregnancy rate per embryo transferred were similar in the very short-term culture group and the short-term culture group (66.7% vs. 68.4%, p =0.44). There was no significant difference in the ongoing pregnancy rate per embryo transferred between the two groups (18, 8% vs. 16.5.%, p =0.74). The miscarriage rate in both groups was comparable ( p =0.77). Limitations, reasons for caution: The small number of women recruited ant the retrospective design of the study, should be recognized as possible sources of bias. Wider implications of the findings: This study showed that the culture time after warming was irrelevant for blastocyst implantation potential, and that the speed of re-expansion was not correlated with clinical outcomes. Embryo transfer timing after warming may be determined by optimizing each laboratory's work flow. Trial registration number: 0